HYDROLYSIS OF CLAY FROM CAPKALA WITH VARIATION OF CHLORIDE ACID CONCENTRATIONS - Wahyuni, Nelly; S., Imelda H.; Arryanto, Yateman; Sutarno, Sutarno (Jurnal Zeolit Indonesia, 2008)
Hydrolysis of clay from Capkala with variation of chloride acid concentratios has been done. Hydrolysis of clay has been conducted by reacting clay in HCl with stirring during 24 hours. Hydrolysis was conducted in several variations of HCl concentration at room temperature. Hydrolyzed clay was characterized by the Atomic Absorption Spectophotometer, Infrared Spectophotometer, and X-ray Diffractometer. The analysis of Spectophotometer of Atomic Absorption was not showed the decreasing of aluminum content of hydrolized clay which is not the extrication of aluminum metal from clay structure. Infrared spectra from hydrolized clay was not showed the eliminated of absorption peak for Al-OH bonds in octahedral layer. Diffractograms of hydrolized clay was not showed the changing angle of 2Î¸ but figuring the increase of intensity of diffraction peak which indicates discharge of pollutant metals from clay structure.